Evaluation Some Immunological Markers in Patients Infected with Hydatid Cysts - Saleem Khteer Al-Hadraawy (Journal of Global Pharma Technology, 2018)
A hydatid cyst is the important disease reported parasite worldwide. The aim of this study was to investigate the PGE2, GM-CSF, TGF- β1 and IL-13 concentration in patients infected with hydatid cyst. We registered 60 patients with Hydatidosis which separated as30 male and 30 female and the control groups consisted of healthy subjects 30 separated as 15 male and 15 female. The results demonstrated that there was a significant increase (P < 0.05) in the PGE2, GM-CSF, TGF- β1 and IL-13 levels, Hydatidosis patients as compared to the healthy group.Key words: Hydatid cyst disease, IL-13, TGF- β1and GM-CSF.